An Assessment of the Economic Transformation of Ughoton (Old Sea Port of Benin Kingdom) From 1440-1897 - Ediagbonya Michael (Britain International for Academic Research (BIAR-Publisher), 2023)
The study examines the economic transformation of Ughoton from 1440-1897. First, it assesses the agricultural activities, trade and crafts before 1440 in Ughoton. It discusses the changes that took place in agricultural activities including farming, fishing and hunting. It also analyzed development of Ughoton as a Benin port during the period of Benin-European trade relations. The study relied on both the secondary and primary sources of data. The primary sources consisted of oral interview and documentary data. The documentary data were sourced from intelligence reports, divisional annual reports, colonial letters, dispatches, government reports and correspondences. These data were obtained from State Archives and Record Services, Benin City and National Archives, Ibadan. The secondary sources includes books, newspaper, articles and periodicals. The study found that the introduction of maize, cassava and tree crops such as oranges, coconuts, tangerine, mangoes after the fifteenth century by the Portuguese boosted economic activity in Ughoton in particular and Benin Kingdom in general. The study also found that the introduction of fishing nets and hooks from the sixteenth century boosted the fishing activities in Ughoton. The study shows that the strategic location of Ughoton on the Benin river enabled it to serve as a Benin port for 4 centuries, which brought much wealth and fame to the kingdom and its monarchy.